Determinant Factors of Dividend Policy in Cooperative Organization - Sugiyanto Sugiyanto; Nur’aeni Nur’aeni; Leli Savitri Dewi (International Journal of Research in Community Services, 2023)
Dividend policy is one of the functions of financial management with regard to the distribution of corporate earnings after tax or the cooperative surplus to the owner. Dividend policy in cooperatives organization is regulated based on regulations and member agreements stipulated in the articles of association and by-laws of the cooperative. The purpose of this study is to analysis the determinant factors of dividend policy in cooperative organization. This study uses research and analysis of descriptive qualitative approach. Data were obtained from 4 cooperatives, where the cooperative determined with consideration of routinely distributing cooperative surplus.The results of the study show that the determinant factors of cooperative dividend policies are found in several additional determinants such as: member participation, cooperative principles, member conditions and regulation, in addition to determinants that have been widely researched and used as guidelines for in general, such as: liquidity, profitability, firm size, capital requirement (leverage), and risk. New findings from the determinants of dividend policy in cooperatives organization such as member participation, cooperative principles, member conditions and regulation need to be studied further with a quantitative research approach, so that the conclusions can be generalized.